2020
DOI: 10.1371/journal.pone.0240961
|View full text |Cite
|
Sign up to set email alerts
|

Game analysis on the evolution of COVID-19 epidemic under the prevention and control measures of the government

Abstract: In this paper, the interaction strategies and the evolutionary game analysis of the actions taken by the government and the public in the early days of the epidemic are incorporated into the natural transmission mechanism model of the epidemic, and then the transmission frequency equations of COVID-19 epidemic is established. According to the cumulative confirmed cases of COVID-19 in the UK and China, the upper limit of the spread of COVID-19 in different evolutionary scenarios is set. Using SPSS to perform lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Since the outbreak of COVID-19, several studies have analyzed the impacts of government policies on the public [28][29][30]. For example, Wei et al (2020) [30] applied the interaction strategies and the evolutionary game analysis of the actions taken by the government and the public. Their study demonstrated that emergency response adopted by the government in the early stages of the pandemic could effectively contain the spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the outbreak of COVID-19, several studies have analyzed the impacts of government policies on the public [28][29][30]. For example, Wei et al (2020) [30] applied the interaction strategies and the evolutionary game analysis of the actions taken by the government and the public. Their study demonstrated that emergency response adopted by the government in the early stages of the pandemic could effectively contain the spread.…”
Section: Introductionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, several studies have analyzed the impacts of government policies on the public [ 28 30 ]. For example, Wei et al (2020) [ 30 ] applied the interaction strategies and the evolutionary game analysis of the actions taken by the government and the public.…”
Section: Introductionmentioning
confidence: 99%
“…This term has some analogies to the mechanism of purely reactive awareness-based models but which do not consider the other factors detailed above [4][5][6][7][8][9][10][11][12]. A similar implementation of this term is often present in the payoffs of imitationbased game-theoretic models [14,16,[22][23][24]. Finally, the last term reduces the payoff to account for the immediate and accumulated social, psychological, and economic costs associated with the adoption of self-protective behaviors [15,47].…”
Section: Modelmentioning
confidence: 99%
“…Several efforts have been proposed across similar research avenues, although with different and narrower angles. For example, imitation mechanisms [14,16,22,23] rely on a population-level modeling that can capture only limited features of such complex behavioral dynamics. Recently, an individual-level imitation-driven mechanism that accounts for the perceived risk of infection and immediate costs for adopting protective behaviors has been proposed and analyzed, showing that it may generate sustained steady oscillations [24].…”
Section: Introductionmentioning
confidence: 99%
“…Kabir et al proposed a novel epidemic model associated with behavioral dynamics under the EGT by considering the two-body system, and they agreed that the funds spent on the individual level as an "emergency relief-package" can reduce the infection and improve quarantine policy success (19). Wei et al established transmission frequency equations, which combined the interaction strategies and the evolutionary game analysis of the actions taken by the government and the public, and found that the emergency response strategy adopted by the government in the early days of the epidemic can effectively control the spread of the epidemic (20). All the above studies combined epidemiological research with game theory, which provided enlightenment for current and future epidemic prevention.…”
Section: Introductionmentioning
confidence: 99%